Ethical Issues in COVID-19 Pandemic - Mohsen Saberi Isfeedvajani; Foroozan Fares; Zahra Ismaili Shahroudi Moqaddam (Baqiyatallah University of Medical Sciences, 2020)
The coronavirus SARS-CoV-2 disease (COVID-19) is the most current life-threating disease that affect health and economic sectors in the world. This pandemic raises weighty and urgent ethical issues that affected patients, health care provider and health care systems. Based on medical ethics textbooks, there are four fundamental ethical principles: The principle of respect for autonomy, the principle of beneficence, the principle of non-maleficence, and the principle of justice. Medical ethics scientists have well explained these principles before with full accuracy and detail. In this review article, we discussed the ethical issues raised during the COVID-19 pandemic. Health inequity and inequality, health care rationing/triage, contact tracing technologies and data privacy, movement restriction and exit strategies, and finally COVID-19 research ethics especially clinical trials and vaccine studies could cause ethical problems during Covid-19 pandemic. In this review article, we discuss about these issues and provide some ethical solutions to these issues